Biochemical correlations among the thermophilic enteric yeasts Torulopsis bovina, Torulopsis pintolopesii, Saccharomyces telluris, and Candida slooffii. - Watson, K (1980)
Spontaneous and drug-induced respiration-deficient mutants were isolated from the thermophilic enteric yeasts Torulopsis bovina and Saccharomyces telluris. The biochemical properties of these yeasts were compared with those of the two naturally occurring respiration-deficient thermophilic yeasts T. pintolopesii and Candida slooffii. Succinate dehydrogenase was not detected in mitochondrial fractions from C. slooffii, but was present in all other species. Cytochrome c oxidase, succinate oxidase, and reduced nicotinamide adenine dinucleotide oxidase were not detected in C. slooffii, T. pintolopesii, and the respiration-deficient mutants. Low-temperature cytochrome spectra revealed the presence of cytochromes aa3, b, c1, and c in T. bovina and S. telluris; cytochromes b, c1, and c in C. slooffii and T. pintolopesii; and cytochromes c1 and c in the spontaneous respiration-deficient mutants. Palmitoleic and oleic acids were the major fatty acids in all the species. It was noteworthy that T. pintolopesii was rich in lauric and myristic acids. CsCl equilibrium centrifugation experiments showed the presence in all the yeasts of a light-buoyant-density (1.6785 to 1.6837-g/cm3) deoxyribonucleic acid band which was identified as mitochondrial deoxyribonucleic acid by its selective elimination on treatment of cells with ethidium bromide. The latter result indicated that the spontaneous respiration-deficient mutants were similar to cytoplasmic petite mutants of S. cerevisiae. Although classical assimilation and fermentation tests indicated that the spontaneous respiration-deficient mutants were strains of T. pintolopesii, it was concluded, on the basis of marked physiological and biochemical differences, that this was not the case.